2002
DOI: 10.1088/0022-3727/35/21/319
|View full text |Cite
|
Sign up to set email alerts
|

Tracking an individual streamer branch among others in a pulsed induced discharge

Abstract: The electro-dynamical properties and the mutual influence of several simultaneously propagating streamers are investigated in a point-to-plane configuration in air at atmospheric pressure under impulse voltage. When a fast and short high voltage pulse is applied to the point, a bunch of streamer branches develops into the interval. Since no previous ionized path has been traced before in the gap, streamers spread in the whole gap, branching while propagating. This behaviour is quite different from streamers un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
35
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 15 publications
12
35
0
Order By: Relevance
“…In the introduction we already mentioned that a higher applied voltage generally results in a higher streamer propagation velocity [2,5,6,9,3,11,4,47,12]. In the streamerlength discussion we showed that for the 2-m reactor the voltage is highest at the beginning and at the end of the reactor, so we would expect the highest streamer propagation velocities there.…”
Section: Streamer Propagation Velocitymentioning
confidence: 95%
See 3 more Smart Citations
“…In the introduction we already mentioned that a higher applied voltage generally results in a higher streamer propagation velocity [2,5,6,9,3,11,4,47,12]. In the streamerlength discussion we showed that for the 2-m reactor the voltage is highest at the beginning and at the end of the reactor, so we would expect the highest streamer propagation velocities there.…”
Section: Streamer Propagation Velocitymentioning
confidence: 95%
“…The majority have used pointplate geometries which are very useful for fundamental streamer research because of optical accessibility and reproducibility [5,22,8,9,38,39,10,3,40,43,44,4,47]. Some used wire-plate geometries [6,7] and only a few have looked at coaxial geometries [2,12,11,52].…”
Section: Electrode Geometrymentioning
confidence: 99%
See 2 more Smart Citations
“…These streamers typically have a velocity in the range of 10 5 -10 7 m · s −1 and a diameter of several hundred micrometers to several millimeters. [5][6][7][8][9][10][11][12][13][14][15] Due to the high energetic electrons that are generated in these non-thermal plasmas, they are very efficient in producing highly reactive radical species. 16,17 These species can consequently react with, for instance, particles in gas streams (for example, pollutants, odor and dust), contamination in water, biological tissue, and material surfaces.…”
Section: Introductionmentioning
confidence: 99%